Lipid mediator n‐3 docosapentaenoic acid‐derived protectin D1 enhances synaptic inhibition of hippocampal principal neurons by interaction with a G‐protein‐coupled receptor. Issue 3 (21st February 2022) - Mikroulis, Apostolos; Ledri, Marco; Ruffolo, Gabriele; Palma, Eleonora; Sperk, Günther; Dalli, Jesmond; Vezzani, Annamaria; Kokaia, Merab
Abstract: Epilepsy is a severe neurological disease manifested by spontaneous recurrent seizures due to abnormal hyper‐synchronization of neuronal activity. Epilepsy affects about 1% of the population and up to 40% of patients experience seizures that are resistant to currently available drugs, thus highlighting an urgent need for novel treatments. In this regard, anti‐inflammatory drugs emerged as potential therapeutic candidates. In particular, specific molecules apt to resolve the neuroinflammatory response occurring in acquired epilepsies have been proven to counteract seizures in experimental models, and humans. One candidate investigational molecule has been recently identified as the lipid mediator n‐3 docosapentaenoic acid‐derived protectin D1 (PD1n‐3DPA ) which significantly reduced seizures, cell loss, and cognitive deficit in a mouse model of acquired epilepsy. However, the mechanisms that mediate the PD1n‐3DPA effect remain elusive. We here addressed whether PD1n‐3DPA has direct effects on neuronal activity independent of its anti‐inflammatory action. We incubated, therefore, hippocampal slices with PD1n‐3DPA and investigated its effect on excitatory and inhibitory synaptic inputs to the CA1 pyramidal neurons. We demonstrate that inhibitory drive onto the perisomatic region of the pyramidal neurons is increased by PD1n‐3DPA, and this effect is mediated by pertussis toxin‐sensitive G‐protein coupled receptors. Our data indicate that PD1n‐3DPA acts directly on inhibitory transmission, most likely at the presynaptic site of inhibitory synapses as also supported by Xenopus oocytes and immunohistochemical experiments. Thus, in addition to its anti‐inflammatory effects, PD1n‐3DPA anti‐seizure and neuroprotective effects may be mediated by its direct action on neuronal excitability by modulating their synaptic inputs.